Coronary artery bypass grafting vs. percutaneous coronary intervention in coronary artery disease patients with advanced chronic kidney disease: A Chinese single-center study - Li, Yang; Hou, Xuejian; Xu, Xiaoyu; Huang, Zhuhui; Liu, Taoshuai; Xu, Shijun; Rui, Hongliang; Zheng, Jubing; Dong, Ran (Frontiers in Surgery, 2023)
Objectives: Aims to compare the contemporary and long-term outcomes of coronary artery bypass grafting (CABG) and percutaneous coronary intervention (PCI) in coronary artery disease (CAD) patients with advanced chronic kidney disease (CKD). Methods: 823 CAD patients with advanced CKD (eGFR<30 ml/min/1.73m2) were collected, including 247 patients who underwent CABG and 576 patients received PCI from January 2014 to February 2021. The primary end point was all-cause death. The secondary end points included major adverse cardiac and cerebrovascular events (MACCEs), myocardial infarction (MI), stroke and revascularization. Results: Multivariable Cox regression models were used and propensity score matching (PSM) was also performed. After PSM, the 30-day mortality rate in the CABG group was higher than that in the PCI group but without statistically significant (6.6%vs2.4%, p=0.0640). During the first year, patients referred for CABG had a hazard ratio (HR) of 1.42 [95% confidence interval (CI), 0.41–3.01] for mortality compared with PCI. At the end of the 5-year follow-up, CABG group had a HR of 0.58 (95%CI, 0.38-0.86) for repeat revascularization, a HR of 0.77 (95%CI, 0.52-1.14) for survival rate and a HR of 0.88(95%CI, 0.56-1.18) for MACCE as compared to PCI. Conclusions: Our study suggests that among advanced CKD patients，CABG showed obviously lower risk for repeat revascularization, a better trend of survival and other adverse events compared with PCI during the long-term follow-up.